2014
DOI: 10.1371/journal.ppat.1004248
|View full text |Cite|
|
Sign up to set email alerts
|

The HIV-1 Envelope Transmembrane Domain Binds TLR2 through a Distinct Dimerization Motif and Inhibits TLR2-Mediated Responses

Abstract: HIV-1 uses a number of means to manipulate the immune system, to avoid recognition and to highjack signaling pathways. HIV-1 infected cells show limited Toll-Like Receptor (TLR) responsiveness via as yet unknown mechanisms. Using biochemical and biophysical approaches, we demonstrate that the trans-membrane domain (TMD) of the HIV-1 envelope (ENV) directly interacts with TLR2 TMD within the membrane milieu. This interaction attenuates TNFα, IL-6 and MCP-1 secretion in macrophages, induced by natural ligands of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Studies motivated by the similarity between the sequence 694 GLRIVFAV 701 and a transmembrane section of the T-cell receptor ␣ subunit demonstrated the interaction of the gp41 TMD with CD3 partners in the TCR complex, resulting in the inhibition of T-cell proliferation (30). More recently, it has been reported that the gp41 TMD may also associate with the Toll-like receptor-2 TMD in the membrane, interfering with the receptor-mediated signaling and decreasing pro-inflammatory cytokine secretion (32). Collectively, these findings suggest that the sequence of the HIV-1 TMD plays critical functions beyond that of anchoring the Env complex to membranes (8 -11), although the structural requirements underlying these distinct functional roles remain to be determined.…”
Section: Left Panel)mentioning
confidence: 99%
“…Studies motivated by the similarity between the sequence 694 GLRIVFAV 701 and a transmembrane section of the T-cell receptor ␣ subunit demonstrated the interaction of the gp41 TMD with CD3 partners in the TCR complex, resulting in the inhibition of T-cell proliferation (30). More recently, it has been reported that the gp41 TMD may also associate with the Toll-like receptor-2 TMD in the membrane, interfering with the receptor-mediated signaling and decreasing pro-inflammatory cytokine secretion (32). Collectively, these findings suggest that the sequence of the HIV-1 TMD plays critical functions beyond that of anchoring the Env complex to membranes (8 -11), although the structural requirements underlying these distinct functional roles remain to be determined.…”
Section: Left Panel)mentioning
confidence: 99%
“…For example, HIV-1 is inhibited and sensed by TRIM5a from nonhuman primates but resistant against the human ortholog because of adaptive mutations in its capsid protein [85]. Furthermore, detection of cytosolic RNA by RIG-I is antagonized by the viral protease [35], and TLR2-mediated and TLR9-mediated sensing are inhibited by gp41 and gp120, respectively [86][87][88]. Finally, it has been shown that the accessory protein Vpr recruits and activates the structure-specific endonuclease regulator SLX4 complex [89].…”
Section: Modulation Of Innate Sensing By Hiv-1mentioning
confidence: 99%
“…In addition to TLR sensing of HIV-1 nucleic acids, some studies provided evidence for a direct recognition of HIV-1 products by surface TLRs. In particular, Reuven and coworkers [13] reported a physical interaction between HIV-1 gp41 and TLR2 in the membrane of murine macrophages. Likewise, a high-affinity, physical interaction between Tat and TLR4-MD2 has been described in monocytes [16].…”
Section: Surface Tlrsmentioning
confidence: 99%
“…However, signaling via TLRs has also been shown to promote HIV-1 infection in innate cells, directly by promoting HIV-1 transcription, or indirectly through cytokine induction [12]. Scattered evidence also suggests that at least some TLRs can sense HIV-1 by physically interacting with HIV components [13][14][15][16]. Overall, increasing evidence points to a functional role of TLRs in HIV-1 disease.…”
Section: Introductionmentioning
confidence: 99%